Accumulated lifecourse adversities and depressive symptoms in later life among older men and women in England: a longitudinal study. Issue 10 (25th October 2020) - Falkingham, Jane; Evandrou, Maria; Qin, Min; Vlachantoni, Athina
Abstract: This paper investigates the association between accumulated major lifecourse adversities and later-life depressive symptoms among older people in England, both at a single point in time (prevalence) and the onset over time during later life (incidence), using data from the English Longitudinal Study of Ageing. Using retrospective data on the experience of major life adversities from childhood onwards, five latent classes were identified: no/few lifecourse adversities (58.6%), lost relationship (27.0%), chained adversities (2.4%), childhood adversities (6.3%) and war-related adversities (5.7%). Older people who had experienced 'chained adversities', 'childhood adversities' and 'a lost relationship' had higher odds of presenting current depressive symptoms in 2006, even after controlling for socio-demographic characteristics, health-risk behaviours and social resources. Longitudinal analysis indicated that amongst respondents who were clear of depression in 2006, those older people who had experienced childhood adversities, a lost relationship and war-related adversities experienced a higher risk of having a new case of depressive symptoms. Results further indicate that women's mental health in later life is more sensitive to earlier life adversities than men's. The study shows that intervention earlier in the lifecourse may have benefits for the individual both contemporaneously and over the longer term.